Between Scylla and Charybdis: Margaret Archer’s social realism - Oliveira, Nuno (2016)
This article aims to compare Archer’s theoretical proposals with those of Giddens or, more precisely, to read Giddens through Archer and vice versa, in a deliberate dialogical attempt that never reaches — and never tries to reach — a synthesis. It is intended, through this comparison, to cast light on certain logical articulations between the two paradigms that may delineate the strengths and weaknesses of social realism as conceived by Archer. For this reason, we put forward three vectors of analysis, through which to set the two approaches against each other: the ontological, systemic and actionalist axes. We conclude by suggesting that certain key proposals in the theory of structuration cannot be neglected, on pain of a theory of morphogenesis falling into a spurious internalism that runs the risk of slipping towards a reductive vision of the articulation between personal emerging capacities and structural emerging properties.